Flash MX - Watrall, Ethan (Sybex, 2002)
Flash MX Savvy teaches designers how to hone their artistic skills, while showing developers how to navigate the ins and outs of ActionScript and other advanced techniques. Topics covered include: creating and developing Flash content to put on your web site; producing compelling interactive content for site visitors; mastering the ins and outs of ActionScript to add advanced interactivity; integrating professional-level audio into your animations; and maximizing Flash's potential when used with other programs.